2021
DOI: 10.3389/fmars.2021.644965
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Ocean Acidification on Carbon and Nitrogen Fixation in the Hermatypic Coral Galaxea fascicularis

Abstract: The supply of metabolites from symbionts to scleractinian corals is crucial to coral health. Members of the Symbiodiniaceae can enhance coral calcification by providing photosynthetically fixed carbon (PFC) and energy, whereas dinitrogen (N2)-fixing bacteria can provide additional nutrients such as diazotrophically-derived nitrogen (DDN) that sustain coral productivity especially when alternative external nitrogen sources are scarce. How these mutualistic associations benefit corals in the future acidifying oc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 79 publications
0
3
0
Order By: Relevance
“…Indeed, dinoflagellates supply glycerol as an energy source for cyanobacterial symbionts found in Montipora cavernosa , providing a steady supply of reductant (e.g., NADPH) and ATP for dinitrogen fixation in the cyanobacteria 60 . Additionally, N 2 fixation by coral-associated diazotrophs, coral calcification, reproduction, and tissue thickening are energy-intensive processes that probably compete for energy deriving from photosynthesis within the coral holobiont 66 . Thus, massive N 2 fixation, together with maintenance of coral reproduction and thickening of coral tissue occurring at the low pH Sites could be absorbing most of the photosynthetic energy from the symbiotic algae, creating an energy deficit that could possibly explain the previously observed decline in net calcification rates of this species along the same pH gradient 24 , 34 .…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, dinoflagellates supply glycerol as an energy source for cyanobacterial symbionts found in Montipora cavernosa , providing a steady supply of reductant (e.g., NADPH) and ATP for dinitrogen fixation in the cyanobacteria 60 . Additionally, N 2 fixation by coral-associated diazotrophs, coral calcification, reproduction, and tissue thickening are energy-intensive processes that probably compete for energy deriving from photosynthesis within the coral holobiont 66 . Thus, massive N 2 fixation, together with maintenance of coral reproduction and thickening of coral tissue occurring at the low pH Sites could be absorbing most of the photosynthetic energy from the symbiotic algae, creating an energy deficit that could possibly explain the previously observed decline in net calcification rates of this species along the same pH gradient 24 , 34 .…”
Section: Discussionmentioning
confidence: 99%
“…For acidification, which mainly focused on pCO 2 elevation, inconsistent results were documented. Some studies demonstrate a decrease in N 2 fixation rates as pCO 2 increased, explained by the reallocation of energy for calcification (Rädecker et al, 2014;Zheng et al, 2021). However, some field studies showed that N 2 fixation rates and diazotrophs in coral holobionts were higher in high pCO 2 sites than low pCO 2 sites (Biagi et al, 2020;Meunier et al, 2021b;Prada et al, 2023), such enhancement of N 2 fixation in space was attributable to the higher N requirements induced by the enhanced photosynthesis under high pCO 2 condition (Biagi et al, 2020).…”
Section: Nitrogen Fixation Of Coral Holobionts Under Stressmentioning
confidence: 99%
“…The extent to which corals adapt to a changing climate relies in part on the genetic variation of Symbiodiniaceae [17,18] and the environmental conditions under which the coral-dinoflagellate mutualisms develop [19,20]. Different Symbiodiniaceae strains or species are likely to differ in their intrinsic adaptive capacity, and stresstolerant traits may evolve in some opportunistic symbiont variants [21].…”
Section: Introductionmentioning
confidence: 99%